Cross-border socio-economic impact of gas terminal projects in the Gulf of Trieste and at Žavlje/Zaule on the Slovenian tourist trade - Tkalčič, Marjan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2010)
Italy plans to erect two gas terminals (LNG terminals) in immediate vicinity of the Slovenian state border. No cross-border impact is indicated in the reports produced by the Italian side, despite high probability of cross-border impacts. The present contribution is an expert assessment of the cross-border impact of the LNG terminals on the Slovenian tourist trade. The impacts of this project on the local environment are presented in a descriptive way, based on the impact assessment scale on tourism. In the discussion section, the mitigating measures are specified which could contribute to reduce the impact.
Keywords: environmental protection; Gulf of Trieste; Italija; Italy; onesnaževanje okolja; plinski terminali; Slovenia; Slovenija; sustainable development; tourism; trajnostni razvoj; Tržaški zaliv; turizem; varstvo okolja